Pengembangan Wisata Spiritual di Desa Pekraman Gelgel Klungkung - I Made Mardika; Agus Kurniawan; Ni Komang Arini Styawati (Postgraduated Community Service Journal, 2021)
Partners and target audiences of PPDM Spiritual Tourism Development in Pekraman Gelgel Village, Klungkung are the Bendesa Adat and community groups 'krama' Pekraman Gelgel Village. Pekraman Gelgel Village was chosen as the target of service because it has the potential to be developed into a model for a spiritual tourism village, received support from the Klungkung Regency government, and submitted an application to be a village under the Postgraduate Program of Warmadewa University. The aim of PPDM is to empower the community in preparing, designing and developing various potentials of their cultural heritage in order to realize Gelgel Pekraman Village as a Spiritual tourism. PPDM is designed for 3 years, the first year program is the preparation of a master plan, online spiritual tourism information, and collaborative tourism management regulatory policies. The solutions offered to overcome these problems are: (1) Assistance in the preparation of infrastructure development plans (masterplan) related to the temple cultural heritage in Pekraman Gelgel Village as a Spiritual DTW, (2) Assistance in preparing information on temple cultural heritage which is packaged into content. tourist information on the website, (3) Assistance in the formulation of policies and rules that integrate the management of temple cultural heritage in Pekraman Gelgel Village as a collaborative Spiritual Tourism. The outputs produced are articles in national journals with ISSN, activity videos, publications in print/online media, increased competitiveness, increased application of science and technology, and improved values in society.